HUBUNGAN KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN MENGAPRESIASI PUISI OLEH SISWA KELAS VIII SMP NEGERI 1 DOLOKSANGGUL TAHUN PEMBELAJARAN 2015/2016 - AMRON ZARKASIH RITONGA (JURNAL ILMIAH SIMANTEK, 2020)
The level of intelligence and proficiency possessed by each individual is certainly not the same. Intelligence is the thing thatattracts the attention of many people to be the benchmark for succeeding or not. Almost everyone thinks intellectualintelligence is a key indicator of one's success. In fact, intellectual intelligence only depends on an individual's ability toreceive, process, store, understand and think about various phenomena. There is still human intelligence that has a profoundeffect on students' learning achievements, namely emotional intelligence. Today, one of the factors that influences lowstudent learning achievement is the lack of attention of teachers and parents in developing their emotional intelligence. Ingeneral, students are less able to control their emotions in doing something, so sometimes doing as they please, going out ofcontrol. In fact, some teachers only pay attention to the intellectual intelligence of students, because they assume by havinghigh intelligence, students will get the maximum learning results. Likewise, parents, have the same assumption, so manystudents do uncontrolled activities, and end up getting disappointing results. Based on the current state of student behavior,it is necessary to review the balancing of intellectual intelligence that students have with their emotional intelligence, in orderto be able to produce resilient and independent students and success in learning for the better. Because emotionalintelligence greatly influences the success that students will achieve, emotional intelligence must be developed widely. Withthe emotional development of students, it is expected that students' learning outcomes will improve especially in Indonesiansubjects, more specifically poetry learning.